The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages and elsewhere. There is a need for a special Officer who could advise patients about future training and change of occupation and direct them into the necessary channels. Local Committees should be set up to survey the industries of the district for suitable employment for disabled persons. Arrangements will be necessary to supplement wages for part-time work and more co-operation between employers and the Ministry of Labour is essential for training and apprenticeship. This will be done best by a special Committee with power to act. It should consist of members from the public health and educational departments, representatives from the Local Trades Council, the Rehabilitation Officers from the Labour Exchange, and those who know the patient personally, the doctor and the social worker. This Committee could undertake its own survey of employment and assess requirements from month to month, setting up small training centres if necessary or making arrangements for training with local firms and industries. 13. Housing. A number of excellent memoranda and pamphlets have been issued on this subject, and it is not within the scope of this document to add to these, or attempt to summarise or criticise them. But the connection between housing schemes and the 28 15X/2/464/1